Determination of trace aflatoxin M1 levels in milk and milk products consumed in Turkey by using enzyme-linked immunosorbent assay - Bakirdere, Sezgin; Yaroglu, Tolga; Tirik, Nihan; Demiroz, Mehmet; Karaca, Abdullah (TAYLOR & FRANCIS LTD, 2014)
Aflatoxin M1 (AFM1) levels in milk and milk products (kasar cheese, tulum cheese, dil cheese, cream cheese, white cheese) consumed in Turkey were determined in this study by using enzyme-linked immunosorbent assay (ELISA). Extraction procedure was optimised to obtain high extraction efficiency. Recovery experiment was also performed to test the suitability of the extraction system and it was observed that % recovery values for AFM1 were higher than 92%. The method used in this study was simple and suitable for the detection of AFM1 in these matrices. Results found from the samples were compared with the requirements of Turkish Food Codex (TFC). As much as 42.16% of cheese samples analysed were contaminated while 61/77 milk samples were found to be contaminated with AFM1 in the range of 0.005-0.410 mu g/L. It was found that five white cheese, one kasar cheese and four milk samples exceeded the criteria of 0.5 g/kg for cheese and 0.05 g/L for milk set by TFC.
Keywords: aflatoxin M1; milk; cheese; enzyme-linked immunosorbent assay (ELISA); RAW-MILK; IMMUNOAFFINITY COLUMN; M-1; CONTAMINATION; CEREALS; Chemistry; Food Science & Technology; Immunology; Toxicology